Metabolomic Investigation of Citrus latifolia and the Putative Role of Coumarins in Resistance to Black Spot Disease - Fernandes, Hocelayne Paulino; Salomé-Abarca, Luis Francisco; Gonçalves Pereira, Rosana; Brandão Seibert, Janaína; Silva-Junior, Geraldo José; Das Graças Fernandes da Silva, Maria Fátima; Choi, Young Hae (Frontiers in Molecular Biosciences, 2022)
Citrus black spot (CBS) is a disease caused by the fungus Phyllosticta citricarpa that affects citrus plants, causing fruit blemish and premature drop that result in severe economic losses in commercial citrus orchards. However, CBS symptoms and effects may vary depending on the citrus species: Citrus limon (lemon) is susceptible and highly affected by the disease, while no CBS-related damage has ever been observed for Citrus latifolia (Tahiti lime), implying that it must be resistant to the disease. The difference in the response to this disease provided the opportunity to gain insight into the metabolites responsible for the resistance by comparison of the metabolomic profiles of these two citrus species. Metabolic variations of C. limon and C. latifolia inoculated with P. citricarpa were analyzed using various metabolomic-based platforms including 1H NMR for overall metabolic profiling, and LC-MS and HPTLC for targeted analysis. The 1H NMR spectra of the samples demonstrated that certain phenolics were strongly induced after pathogenic inoculation, especially in the resistant species. The induced phenolics were identified from C. latifolia by further 1H NMR, LCMS and HPTLC analysis yielding six prenylated and methoxy coumarins, i.e., 5,7-dimethoxycoumarin, 5-geranyloxy-7-methoxycoumarin, 7-geranyloxycoumarin, 8-methoxypsoralen, 5,8-dimethoxypsoralen and 5-geranyloxypsoralen. These isolated coumarins and a coumarin-rich fraction they were isolated from were tested against the fungal pathogen, P. citricarpa to evaluate their activity. None of the individual coumarins exhibited a significant inhibition. while the fraction exhibited a strong antifungal activity suggesting the synergistic interaction of its components. To obtain further insight into the roles of these compounds in the plant defense, the possible mechanisms of the individual coumarins were tested using an in-silico model, the PASS Online Tool; the analysis showed that each coumarin appeared to have a unique defense mechanism, even with very slight variations in the chemical structures. The results could provide evidence of the existence of a complex plant defense mechanism consisting in a multitude of synergistic interactions between compounds.